CD11b+Gr‐1dim Tolerogenic Dendritic Cell–Like Cells Are Expanded in Interstitial Lung Disease in SKG Mice. Issue 12 (9th November 2017) - Sendo, Sho; Saegusa, Jun; Okano, Takaichi; Takahashi, Soshi; Akashi, Kengo; Morinobu, Akio
Abstract : Objective: SKG mice develop interstitial lung disease (ILD) resembling rheumatoid arthritis–associated ILD in humans. The aim of this study was to clarify the mechanism underlying the lung pathology by analyzing lung‐infiltrating cells in SKG mice with ILD. Methods: We assessed the severity of zymosan A (ZyA)–induced ILD in SKG mice histologically, and we examined lung‐infiltrating cells by flow cytometry. Total lung cells and isolated monocytic myeloid‐derived suppressor cells (MDSCs) were cultured in vitro with granulocyte–macrophage colony‐stimulating factor (GM‐CSF) and interleukin‐4. The proliferation of 5, 6‐carboxyfluorescein diacetate N ‐succinimidyl ester–labeled naive T cells cocultured with isolated CD11b+Gr‐1 dim cells and MDSCs was evaluated by flow cytometry. CD11b+Gr‐1 dim cells were adoptively transferred to ZyA‐treated SKG mice. Results: MDSCs, Th17 cells, and group 1 and 3 innate lymphoid cells (ILC1s and ILC3s) were increased in the lungs; the proportion of these cells varied with ILD severity. In this process, we found that a unique cell population, CD11b+Gr‐1 dim cells, was expanded in the severely inflamed lungs. Approximately half of the CD11b+Gr‐1 dim cells expressed CD11c. CD11b+Gr‐1 dim cells were induced from monocytic MDSCs with GM‐CSF in vitro and were considered tolerogenic because they suppressed T cell proliferation. These CD11b+Gr‐1 dim cells have never been described previously, and we termed them CD11b+Gr‐1 dim tolerogenic dendritic cell (DC)–like cells. Th17 cells, ILC1s, and ILC3s in the inflamed lung produced GM‐CSF, which may have expanded CD11b+Gr‐1 dim tolerogenic DC–like cells in vivo. Furthermore, adoptive transfer of CD11b+Gr‐1 dim tolerogenic DC–like cells significantly suppressed progression of ILD in SKG mice. Conclusion: We identified unique suppressive myeloid cells that were differentiated from monocytic MDSCs in SKG mice with ILD, and we termed them CD11b+Gr‐1 dim tolerogenic DC–like cells.